The effect of different resistance training protocols equalized by time under tension on the force-position relationship after 10 weeks training period - Martins-Costa, H. C.; Lanza, M. B.; Diniz, R. C.; Lacerda, L. T.; Gomes, M. C.; Lima, F. V.; Chagas, M. H. (European Journal of Sport Science, 2022)
This study investigated the impact of 10 weeks performing two equalized resistance training (RT) protocols that differ only by repetition duration and number in the force-position and EMG-position relationship. Participants performed an equalized (36 s of time under tension; 3-4 sets; 3 min between sets; 50-55% of one-repetition maximum; 3x week) RT intervention on the bench press and the only different change between protocols were repetition number (RN; 12vs.6) or duration (RD; 3s vs. 6s). Two experimental groups (RN12RD3, n= 12; and RN6RD6, n=12) performed the RT, while one group was the control (Control, n=11). Maximal isometric contractions at 10%, 50%, and 90% of total bench press range of motion were performed pre- and post-RT, while electromyography was recorded. It was demonstrated an increase in isometric force (+14% to 24%, P<0.001) shifting up the force-position relationship of the training groups after RT, although no difference between training groups compared to Control. Neuromuscular activation from pectoralis major presented an increase after training for both RT groups (+44%; P<0.001) compared to Control. However, although not significantly different, triceps brachii also presented an increase depending on the protocol (+25%). In conclusion, 10 weeks of an equalized RT with longer RN and shorter RD (or opposite) similarly increases the ability to produce maximal isometric force during the bench exercise across different angles, while neuromuscular activation of the pectoralis major partially explained the shift-up of the force-position relationship after training.